Rehabilitation of Perpetrators of International Crimes – Myth or Reality? Case Study of the International Criminal Tribunal for Former Yugoslavia - Strupinskienė, Lina; Jankauskaitė-Činčė, Indrė (Politologija, 2022)
Of the 92 persons convicted at the International Criminal Tribunal for Former Yugoslavia (ICTY), 60 have already served their sentences and were released. Even though perpetrators’ rehabilitation and their public behaviour in post-conflict environments are essential for countering denial, establishing an authoritative version of the truth, and sustainable reconciliation, we still know little about what happens after they return to their communities. This article attempts to examine ICTY convicts’ rehabilitation by assessing the quality and the result of existing rehabilitation programs (e.g., how much the public behaviour of those released matches the expectations of the victim’s community, what their relationship is with their guilt and crimes committed). Aside from secondary sources, it draws on 23 semi-structured interviews with victims of war, representatives from victims’ associations, and human rights advocates from the region. It finds that in the context of the absence of specialized rehabilitation programs and lack of oversight of the post-conviction stage at the ICTY, the convicted perpetrators return to communities that support and enable them. Hailed by specific enthusiastic audiences back home, ICTY convicts often fulfil their expectations, closing a vicious circle that dramatically curbs the individual or collective transformative potential of their punishment regarding reckoning with the past and moving towards reconciliation.
Keywords: International Criminal Tribunal for Former Yugoslavia; international crimes; rehabilitation; transitional justice; reconciliation